1989 : Little Critic Pamphlet Two. (London : Victoria Miro Gallery, 1989)
Schöttle, Rüdiger ; Nannucci, Maurizio ; Worringer, Wilhelm ; Bernstein, Thomas ; Abramovic, Marina ; Rückriem, Ulrich ; Charlton, Alan ; Blacker, Kate ; Toren, Amikam ; etc.
1989, Victoria Miro Gallery, London, 1989
boek